THE USE OF DISCOVERY LEARNING USING GEOMETRY MODEL AS MEDIA IN IMPROVING LEARNING OUTCOME IN GEOMETRY FOR FIFTH GRADE STUDENTS OF SD NEGERI 2 DEPOKREJO IN THE ACADEMIC YEAR OF 2016/2017. - FIRDHAUS, RYANDI; TRIYONO, TRIYONO; NGATMAN, NGATMAN (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: The Use of Discovery Learning using Geometry Model as Media in Improving Learning Outcome in Geometry for fifth grade students of SD Negeri 2 Depokrejo in the academic year of 2016/2017. The objective of this research is to improve learning outcome in geometry for fifth grade students of sd negeri 2 depokrejo. This research is a collaborative Classroom Action Research (CAR). Subjects of the research were students of fourth grade and its teacher of V SD Negeri 2 Depokrejo. The data were qualitative and quantitative. Techniques of collecting data were learning outcomes test, observation, and interview. It was conducted within three cycles. Each cycle consisted of planning, action, observation, and reflection. The results of this research show that the use of discovery learning using geometry model as media can improve students? learning outcome for fifth grade students of SD Negeri 2 Depokrejo in the academic year of 2016/2017.